Improvement of Pedagogical Technologies for the Development of Creative and Critical Thinking in Young Students - Bakhtybaevich, Abatov Jumabay (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article emphasizes the importance of teaching methods in organizing physical education classes in secondary schools .